Growth and Biomass Accumulation of Mucuna bracteata in Response to Rhizobium sp Biofertilizer Dosages as Legume Cover Crop in Oil Palm Plantation - Siregar, Romi Dongoran; Kusumawati, Anna; Fiqi, Muhammad (Jurnal Biologi Tropis, 2026)
Effective ground-cover management in oil palm plantations is essential for limiting soil erosion, suppressing weed growth, and sustaining soil fertility. Among available options, the legume cover crop (LCC) Mucuna bracteata stands out for its fast growth rate and its ability to fix atmospheric nitrogen biologically through a symbiotic relationship with Rhizobium sp. This study was designed to identify the most effective dose of Rhizobium sp biofertilizer for supporting the growth and biomass accumulation of Mucuna bracteata as an LCC in oil palm plantations. It was carried out in the practice garden of Politeknik LPP Yogyakarta, located in Wedomartani, between April and June 2022, applying a non-factorial Randomized Block Design (RBD) that consisted of four treatment levels (0, 2, 8, and 15 g/polybag) with three replicates each, yielding a total of 12 experimental units. The resulting data were subjected to ANOVA, and treatment means were compared through the Least Significant Difference (LSD) test at a 5% significance threshold. The analysis revealed that Rhizobium sp biofertilizer application had a significant effect on every parameter examined. Among the treatments, the 15 g/polybag dose (R3) delivered the highest nodulation and biomass values, with root nodule counts reaching 19.22, nodule weight of 1.93 g, fresh shoot weight of 36.97 g, dry shoot weight of 9.16 g, fresh root weight of 14.01 g, and dry root weight of 2.03 g. At seven weeks after planting, plant height (150.00 cm) and leaf count were significantly greater than the untreated control (142.00 cm; 30.56 leaves), although no significant differences were detected among the biofertilizer dose levels themselves. Taken together, these results support applying Rhizobium sp biofertilizer at 15 g/polybag to optimize the establishment of Mucuna bracteata as an LCC within oil palm nursery systems.